THE INFLUENCE OF MARQUEE PLAYER TOWARD PURCHASE INTENTION OF MERCHANDISE TEAM (CASE STUDY : MICHAEL ESSIEN WHO JOINED PERSIB BANDUNG) - Mochamad Eri Nugraha; Deddy Saefuloh (Politeknik Negeri Bandung, 2018)
The development of a massive football, at first just ordinary game, developed into a commercial sport. This situation encourages every football team needs to have professional management. Now in Indonesia, every team strives to create a more optimal management. Financial conditions become a team success parameter. Therefore, various strategies create to maximize the financial condition, one of them with increasing sales of merchandising team. The phenomenon about contracting marquee player as one of the efforts to improve team performance and interest on purchasing merchandise. Michael Essien was one of those who joined the PERSIB Bandung. Joining ths player is able to attract the attention of Indonesian football, especially supporting PERSIB. In this study, the researchers wanted to find out whether there are significant influence Michael Essien who perform an indirect endorsement against purchase intention. Questionnaire and interview are the way to collecting primary data. Based on the results of data analysis presented to the respondent which is PERSIB supporter at 553 respondents and interview to the official merchanddise store. The results obtained, amounting to 23.2% any endorsement of Michael Essien to purchase intention. The dimension of power was the most influential dimension, followed by the dimension of credibility and aattractiveness.